Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Ketahanan Pangan Dan Peternakan Kabupaten Kediri - Nova Puspitaningrum; Edy Suwasono; Zaenul Muttaqien (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine how the influence of Leadership Style, Work Environment, and Work Discipline on Employee Performance at the Department of Food and Livestock Security of Kediri Regency. By using non-probability sampling with sampling method using purposive sampling technique as many as 66 respondents, and using interview research methods, questionnaires, observations, and library studies. For data analysis techniques in this study using validity test, reliability test, classical assumption test, multiple linear regression analysis test, t test, F test, coefficient of determination test (R2 ) using SPSS For Windows version 25.0. Based on the results of the study showed that the results of the t-test of the Leadership Style variable (X1) had a partially significant effect on employee performance by getting a Sig value. 0.001 < 0.05, the work environment variable (X2) has a partially significant effect on employee performance with the value of Sig. 0.000 < 0.05. While the results of the F test indicate that the Leadership Style (X1), Work Environment (X2), and Work Discipline (X3) have a partially significant effect on Employee Performance at the Food and Livestock Security Office of Kediri Regency with a value of Sig. 0.000 < 0.05.